PENYESUAIAN DIRI KORBAN PERDAGANGAN ANAK - -, Musawwir; -, Syawaliah (Jurnal Ilmiah Ecosystem, 2017)
This is a qualitative research, the objectives are to know how the self-image of the child trafficking’s victims, the mind-set and the self adjustment formed, and the psychological impact experienced by the victims.The method of this research is structured interview method, which refers to the research’s focus that have been made before. Subject of this research are three victims of child trafficking.The result of this research shows that: (1) Most of the subjects have a negative selfimage; (2) The mind-set formed on the victims are influenced heavily by the judgement of the people around them, and then influenced the victims self adjustment on the daily life, and generally all victims are not able yet to do a good self adjustment; (3) the psychological impacts which experienced by the victims are trauma, which have a similier with perpetrator, being agressive, and even frustration.